Working capital and R&D smoothing: Evidence from the Tel Aviv stock exchange - Ahmad Alkhataybeh (Journal of Applied Economics, 2021)
This paper proposes new tests for financing constraints on R&D investment by directly examining the role played by working capital in smoothing the R&D expenditures of firms listed on the Tel Aviv stock exchange. It emphasizes the importance of working capital, not only for use but also as a source of funds. The findings offer new evidence for why levels of liquidity are important for R&D-intensive firms. Working capital alleviates the effects of transient finance shocks on the level of R&D, thereby averting the high adjustment costs that accompany changes in R&D.
Keywords: 330; Working capital; financing constraints; R&D investment